Anton Martin Slomšek in vprašanje enotnosti slovenskega kulturnega prostora - Ogrin, Matija (Slavistična revija, 2012)
This article presents Slomšek's efforts towards linguistic and cultural integration of the Slovene lands between 1821 and 1862. The prominence of the Slovene cultural and geographic space in Slomšek's works is presented by using his correspondence and travel writings, with a special view to his works on a unified Slovene literary language and his creative writing, in particular his poems.
Keywords: 19.st.; 19th century; geolinguistics; geolingvistika; knjižni jezik; literarna geografija; literary geography; Slomšek, Anton Martin, 1800-1862; Slovene; Slovene literary language; Slovene literature; slovenska književnost; slovenski literarni prostor; slovenščina; space of Slovenian culture; standard language